Determinants of stunting in children aged 0-59 months in three regions of Burkina Faso - Ella W. R. Compaore; Ousmane Ouedraogo; Prisca E. Bationo; Korotoumou Traore; Ezeckiel Birba; Pascal Nakelse; Ollo F. Kambou; Boureima Ouedraogo; Abdoul Aziz D. Ilboudo; Souleymane Tirogo; Estelle A. Bambara; Mamoudou H. Dicko (BMC, 2024)
Abstract The Sahel is a region particularly characterized by undernutrition in several forms. In Burkina Faso, where several interventions have been carried out across the past several years, the nutritional situation of children under five years of age is still characterized by persistent stunting in the Est, Sahel, and Cascades regions. This study aims to understand the factors associated with the high prevalence of chronic malnutrition in these regions. National nutrition survey data as well as data from the Ministry of Water and Sanitation were used for bivariate and multivariate statistical analyses to identify factors statistically associated with stunting in children aged 0-59 months who participated in the national nutritional surveys from 2009 to 2019. Around one in ten mothers in all regions had no schooling at all. The improving of IYCF practice has a positive impact on the reduction of the prevalence of chronic malnutrition among children in the Cascades, Est and Sahel regions. In the three target regions, gender and province were significantly associated with stunting. Fever, diarrhea, vitamin A supplementation, household size, and maternal education level were also associated with stunting but only in the Sahel and Cascades regions. Overall, the results of the study show that the fight against stunting must be carried out in a multisectoral approach and target certain provinces particularly because stunting is not uniformly present in all provinces.